Pengaruh Pendidikan Dan Disiplin KerjaTerhadap Kinerja Karyawan Pada Pt. Tiga Pilar Sejahtera Food Tbk Sragen - Rahayu, Lanjar Puji, Imron Rosyadi, SE, M.si (2016)
The purpose of this study was to determine the effect of education and discipline work significantly to the performance of employees at PT Tiga Pilar Sejahtera Food Tbk Sragen. The population in this study were all employees of PT Tiga Pilar Sejahtera Food Tbk Sragen, totaling 100 people. Respondents were drawn as many as 100 people, so all members of the population sampled (study population). Data analysis method used is the classic assumption test, multiple linear regression, goodnes of fit, and t test. The results of this study prove that partially education (X1), and a discipline work (X2) together have a significant impact on employee performance (Y). Later analysis of the coefficient of determination (Adjusted R Square) education variables (X1) and a discipline work (X2) effect by 37,8% to variable employee performance (Y), while the remaining 62,2% is explained by other factors outside the model